Body My House: May Swenson's Work and Life - Gantt, Patricia M. (Utah State University, University Libraries, 2006)
The first collection of critical essays on May Swenson and her literary universe, Body My House initiates an academic conversation about an unquestionably major poet of the middle and late twentienth century. Includes many previously unpublished Swenson poems. Essays here address the breadth of Swenson's literary corpus and offer varied scholarly approaches to it. They reference Swenson manuscripts---poems, letters, diaries, and other prose---some of which have not been widely available before. Chapters focus on Swenson's work as a nature writer; the literary and social contexts of her writing; her national and international acclaim; her work as a translator; associations with other poets and writers (Bishop, Moore, and others); her creative process; and her profound explorations of gender and sexuality. The first full volume of scholarship on May Swenson, Body My House suggests an ambitious agenda for further work. Between the 1950s and the 1980s, May Swenson produced eleven volumes of poetry, received many major awards, was elected chancellor of the Academy of American Poets, and was acclaimed by writers in virtually every school of American poetry.